1700 Clinical phenotype and outcome of hepatitis E virus associated neuralgic amyotrophy (hev-na); an international multicentre retrospective comparative study. (1st December 2017) - Van Eijk, JJ; Dalton, Harry R; Ripellino, P; Madden, Richie G; Jones, C; Fritz, M; Gobbi, C; Melli, G; Pasi, E
Abstract : Background: HEV-NA may have a distinct clinical phenotype and outcome compared to cases of NA without HEV infection. Methods: Cases of NA were identified in 11 centres from 7 countries, with retrospective analysis of demographics, clinical/laboratory findings, treatment and outcome. HEV-NA cases were compared to NA cases without evidence of HEV infection. Findings: 57 HEV-NA and 61 NA without HEV cases were studied. 56/57 of HEV-NA cases were IgM positive (53 IgG positive). In 36 HEV RNA was recovered from the serum and in one from the CSF (all genotype 3). 51/57 HEV-NA cases were anicteric (median ALT was 259 IU/L: range 12–2961). In 6 the liver function tests (LFT) were normal. HEV-NA cases were more likely to have bilateral involvement (p<0.001), damage outside the brachial plexus (p<0.01), reduced reflexes (p=0.03), sensory symptoms (p=0.04) with more extensive damage to the brachial plexus. There was no difference in outcome between both groups at 12 months. Interpretation: Patients with HEV-NA are usually anicteric with modest rises in ALT and have a distinct clinical phenotype. Involvement outside the brachial plexus is more common. Patients presenting with NA should be tested for HEV, irrespective of LFT. Prospective treatment/outcome studies of HEV-NA are now warranted.